Investigation of physical-chemical indices of complex action cream for treating wounded process of wounded servicemen - V. O. Tarasenko; L. L. Davtian (Zaporozhye State Medical University, 2018)
The aim of the work was to study the physical-chemical parameters (colloid stability, thermal stability, osmotic activity, homogeneity and pH) of a complex action cream for local treatment of wounds, with subsequent establishment of compliance with State Pharmacopoeia of Ukraine requirements for this dosage form.Materials and methods. In carrying out experimental studies, the authors used active pharmaceutical ingredients - metronidazole, miramistin (gift sample from Dr. Reddy's labs, Hyderabad, India), anesthesine (Merck, Germany), plant extracts (Aromatika, Ukraine) and auxiliary substances - propylene glycol, glycerol (Loba Chemie Pvt. Ltd., Mumbai, India), polyethylene oxide-400, monoglycerol stearate, cetostearyl alcohol, vaseline oil (Sigma-aldrich, Germany).Physical-chemical parameters of the cream were determined according to generally accepted procedures according to State Pharmacopoeia of Ukraine.The studies were carried out in five series (five samples each). Statistical processing of the results was carried out with the help of Statistica 6.0 package (StatSoft Inc., USA).Results. In vitro experiments using dialysis through a semipermeable membrane, it was determined that the test samples exhibit osmotic activity for 24 hours. After 24 hours exposure, the osmotic activity is 110.7 ± 4.23% and 118.3 ± 4.9%, respectively, for samples of placebo cream and cream. Screening of data on the determination of acid-base balance showed that the pH values of all the test samples of the cream lie in the range from 6.5 to 7.5 and correspond to the pH of the wound. The test to determine the uniformity of the cream showed that all samples are uniform at different storage temperatures for 24 months.Experimental studies of the thermo- and colloidal stability of the cream samples, obtained both immediately after manufacture, and those stored for 24 months under natural conditions and at temperatures recommended by State Pharmacopoeia of Ukraine, showed that no separation was observed in one tube. All samples were stable during storage, which is especially important for emulsion systems.Conclusions. Physical-chemical studies have shown that colloid stability, thermal stability, osmotic activity and pH of the cream meet the established requirements for this dosage form.